Gender perceptions of work-life balance: management implications for full-time employees in Australia. (April 2013) - Fujimoto, Yuka; Azmat, Fara; Härtel, Charmine E.J.
This study reports on gender perceptions of work–life balance based upon a qualitative study carried out among 437 full-time working men ( N =245) and women ( N =192) in the Australian workforce in 2008. The participants were randomly selected from a wide range of occupations, and their perceptions of: (a) non-work issues; (b) work–life conflicts; (c) organisational support for WLB; (d) desired WLB options; and (e) management treatment were investigated. Findings indicate significant gender differences in all areas studied. As this research provides a holistic view of the different gender perceptions of WLB, the findings have important implications for mobilising workplace support for men and women.